Integrating Artificial Intelligence in urban redesign: A collaborative approach to post-war design phases - I. Alshafei; R. Almashhour (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: This study explores the phased approaches of post-war urban re-design to present a collaboration between Artificial Intelligence and traditional processes for post-war urban recovery. A hybrid approach enables stakeholders to actively define their city's future by simulating several re-design scenarios utilizing AI data management. This interactive representation of possible results enables well-informed decision-making, where the advantages and limitations are carefully considered, guaranteeing that the re-design aligns with the requirements and needs of the local communities. This integrative method promotes openness and a feeling of responsibility, establishing the basis for resilient urban environments that emerge from conflict.METHODS: The study establishes a foundation for using Artificial Intelligence technologies to solve complex urban development challenges by critically examining existing approaches for urban re-design after the war and promoting interventions powered by Artificial Intelligence-driven processes. This study aims to contribute to the field of post-war rebuilding of urban landscapes by developing a solution that can be generalized. This study adopts a qualitative methodology approach to investigate the possible integration of Artificial Intelligence in re-designing urban landscapes post-war. The methodology is structured to examine existing approaches and studies of post-war urban recovery, compare traditional and AI-assisted approaches, and propose a hybrid approach that combines both. The study structure is a literature review and theoretical approach development, data collection, and analysis, depending on multiple sources, including government reports and academic research, as well as hybrid approach development.FINDINGS: The discussion provides theoretical evidence of the potential advances in this empirical approach, highlighting the efficiency improvements achievable by using Artificial Intelligence technologies in a hybrid phased approach that integrates traditional post-war processes with Artificial Intelligence -assisted ones. The study also highlights the importance of ethical considerations in Artificial Intelligence restoration procedures, addressing acceptance, community involvement, and cultural heritage safeguarding concerns. This emphasis on ethics reassures the audience about Artificial Intelligence's responsible and conscientious use in post-war re-design.CONCLUSION: The study explores the potential integration of Artificial Intelligence in re-designing postwar urban landscapes. It compares conventional methods of urban revival with innovative Artificial Intelligence-supported methods to determine the advantages of utilizing Artificial Intelligence in post-war urban re-design. Traditional techniques for gathering data, allocating resources, and engaging the community have many challenges that negatively affect the effectiveness of re-designing and re-design measures. This study suggests that integrating Artificial Intelligence with traditional strategies can help overcome these challenges by analyzing extensive datasets, which leads to effective decision-making. A hybrid approach combining conventional and Artificial Intelligence-supported methods is suggested to improve the resiliency and sustainability of the re-designing process. It aims to enhance resource distribution and strategic planning through Artificial Intelligence-assisted strategies.